Formação de educadores do campo proposta pelo curso de Pedagogia da Terra PRONERA/UFMA - Coelho, Leyse Mayara Santos (2015)
This research deals with the proposal for a teacher training course held by the social peasant movements, identifying the theoretical and methodological frameworks that support the Rural Education. The research subject is the political-pedagogical proposal contemplated the course of degree in Pedagogia da Terra (Field Pedagogy) developed by the Universidade Federal do Maranhão (UFMA) through the Programa Nacional de Educação na Reforma Agrária (National Program of Education on Agrarian Reform) (PRONERA), revealing the principles and conceptions guiding the formation of the land educator. This research has qualitative character, carrying out through documentary and bibliographic intepretative analysis. To better understand, was used also semi-structured interviews with the subjects who participated in the operation of the course of Pedagogia da Terra PRONERA-UFMA. Bibliographical research allowed us to understand the forms of organization and control strategies outlined by the movements of the field throughout the history of Brazil, and understand the construction process of the educational project for the peasants people. The educational practice of the movements of the field are ways to pressure the Government to implement public policies aimed at land reform, education and other rights. The investigation showed the existence of different projects of education and teacher training: one designed in accordance with the neoliberal ideas and other produced throught the mobilization of individuals who lived and work in the field. Among the most important achievements station the Diretrizes Operacionais para a Educação Básica nas Escolas do Campo (Operational Guidelines for Basic Education in Rural Schools), in addition to PRONERA, where to systematize various educational projects. The authors that supported this research are: ARROYO (1999, 2010); LDB (1996); Diretrizes Operacionais para a Educação Básica nas Escolas do Campo (2001); CALDART (2004, 2009, 2000, 2008); COUTINHO (2009); DAMASCENO (1996, 1993); DELGADA (2005, 2010); FERNANDES (2004, 2005, 2001); MOLINA (1992, 2004); RIBEIRO (2010) Complementing the understanding of the educational project of social movements, the documentary analysis of the training proposal of the Pedagogia da Terra Course (UFMA) and education legislation enabled the identification of intentions and formative principles the oppose the hegemonic conception of education, which devalues country culture. However, the proposal of said course introduces innovative educational alternatives the recognize the specificities belonging to peasant populations.